Trends in Sexually Transmitted Infection Cases in HIV Populations in Indonesia: Need Firm Roadmaps and Actions - Setyowatie, Lita; Widasmara, Dhelya (Asian Journal of Health Research, 2024)
Human immunodeficiency virus (HIV) infection and sexually transmitted infections (STIs) remain a public health problem and extend to social, economic, and cultural issues. HIV cases in the Southeast Asia region account for 10% of the total global HIV burden. In Indonesia, there are five provinces with the highest number of HIV cases as of December 2021, including DKI Jakarta (73,442), East Java (68,112), West Java (49,435), Central Java (42,012), and Papua (40,277). In Indonesia in 2021, the number of people living with HIV (ODHIV) reported was 36,902 and in 2022 up to the third quarter (July - September 2022) there were 34,213 people. New HIV infections in Indonesia continue to decline, in line with the global decline in new HIV infections. However, this decline has not been as large as expected.